Productivity of organic Cichorium intybus produced with alternative substrates - Uchôa, Thays Lemos (2018)
The objective of this work was to evaluate alternative substrates in the quality of seedlings and in the productivity of chicory in organic cultivation. The experiment conducted in two phases: plant nursery and field, in June 2016. The experimental field is located at Seridó Ecological farm, in Rio Branco, Acre. The experimental design was a randomized block with five treatments and four replications. The treatments constituted by the Golden commercial substrate used as control and by four other alternative substrates: soil (30%), organic compound (30%); Soil conditioner (30%), coal (10%), natural thermophosphate (1.5 kg m-3), dolomitic limestone (1.0 kg m-3) and potassium sulphate (1.0 kg m-3). What differentiated them was the substitution of the conditioner: Carbonized rice husk; Coconut fiber; Fiber of the stem of ouricurí palm (Attalea phalerata) or Cork decomposed of kapok (Ceiba pentandra). The cultivar used was Sugar loaf. At 22 days after sowing, the seedlings evaluated to obtain the quality index and at 60 days after transplanting to the field the total fresh mass, commercial, total dry, commercial and total and commercial productivity were evaluated. The substrates containing kapok and coconut fiber had better performance for root dry mass and Dickson quality index in the seedlings phase, total fresh mass, total and commercial dry mass and total field productivity.